Gambaran Kejadian Penyakit Jantung Koroner Pada Penderita Yang Dirawat Inap Di RSUD Labuang Baji Makassar Tahun 2021-2022 - Onggeng, Sitti Fatimah; Amiruddin, Tedy; Thamrin, Rahmawati (Fakultas Kedokteran Universitas Bosowa, 2025)
Coronary heart disease is a disease caused by narrowing of the coronary arteries by atherosclerotic plaques, so that the supply of nutrients and oxygen to the heart muscle is reduced. Currently CHD is the leading cause of death for both men and women. Various risk factors are thought to contribute to CHD, some of which are modifiable but others are not. This study aims to describe the incidence of coronary heart disease based on (1) age (2) smoking (3) hypertension (4) diabetes mellitus (5) obesity. This research was conducted on 51 samples of patients with coronary heart disease who were hospitalized at RSUD Labuang Baji Makassar in 2021-2022. This study used a descriptive observational method using secondary data in the form of medical records of patients with coronary heart disease who were hospitalized at RSUD Labuang Baji, Makassar. Data analysis was done manually with Microsoft Excel.The results of this study show the distribution of the frequency of coronary heart disease patients who are hospitalized at RSUD Labuag Baji Makassar in 2021-2022, namely: (1) Most CHD sufferers are aged over 40 years (82.4%), (2) More sufferers are did not smoke (82.4%), (3) more CHD patients with hypertension (76.5%), (4) more patients were not accompanied by diabetes mellitus (64.7%), (5) more patients with CHD accompanied by obesity (56.9%). The conclusion of this study, most patients with coronary heart disease are over 40 years old, do not smoke, have hypertension, do not have diabetes mellitus, and are obese.